Identification of the prepared foods promising for dietary folate intake in Beijing, China. Issue 12 (3rd November 2020) - Islam, Md Shariful; Mehmood, Shahid; Zhang, Chunyi; Liang, Qiuju
Abstract: The aim of the present study was to analyze folate content and composition in foods consumed daily by Chinese people. The concentration of seven folate derivatives in sixty‐four selected foods was determined by a liquid‐chromatography tandem‐mass spectrometry method. The total folate levels ranged from 0.28 to 129 µg/100 g fresh weight, with an average of 21.18 μg/100 g. The highest folate content was found in boiled egg yolk and waxy corn (>120 µg/100 g), abundant folate levels in cooked vegetables such as hot pepper, spinach, soybean sprout, stem lettuce, coriander, and broccoli (44–72 µg/100 g), and lowest in Coca Cola (0.28 µg/100 g). 5‐Methyl‐tetrahydrofolate was the major folate derivative in various foods, accounting for 72% of the total folates on average, with the highest being 90% in egg yolk. These data will enable estimation of the daily folate intake and allow dietary recommendations to improve folate status in humans. Abstract : Folate content and composition in 64 foods commonly consumed in China including cereals, vegetables, fruits, eggs, meat, fish, and beverages were determined by LC‐MS/MS. The total folate levels ranged from 0.28 to 129 µg/100 g fresh weight, with an average of 21.18 μg/100 g.